2016
DOI: 10.1586/17446651.2016.1130620
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertension in diabetes: a contemporary approach with a focus on improving cardiovascular outcomes

Abstract: Diabetes mellitus and hypertension are interrelated conditions that predispose patients to cardiovascular disease. The 2015 American Diabetes Association guidelines recommend a blood pressure goal of <140/90 but indicates that a lower goal can be set for some individuals if this can be achieved without undue burden. Renin angiotensin system blockers remain the main stay of treatment in hypertensive diabetics together with lifestyle interventions. Guidelines indicate that combination therapy may be initiated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although it was initially illustrated that among all antidiabetic medications with effect on hypertension (DPP4 inhibitors, GLP-1RAs, and SGLT2-i), the most significant decrease was observed in patients treated with GLP-1 RAs [ 71 ], a recent meta-analysis indicated that SGLT2-i have a more considerable effect [ 72 ].…”
Section: Current Antidiabetic Drugs and The Influence Of Hypertensionmentioning
confidence: 99%
“…Although it was initially illustrated that among all antidiabetic medications with effect on hypertension (DPP4 inhibitors, GLP-1RAs, and SGLT2-i), the most significant decrease was observed in patients treated with GLP-1 RAs [ 71 ], a recent meta-analysis indicated that SGLT2-i have a more considerable effect [ 72 ].…”
Section: Current Antidiabetic Drugs and The Influence Of Hypertensionmentioning
confidence: 99%
“…According to a research conducted, the prevalence of obstructive sleep apnea has been estimated to be more than two-thirds of patients with resistant hypertension 35 . Also, diabetes mellitus have been grately associated with resistant hypertension [36][37][38] .…”
Section: Resistant Hypertension Comorbiditiesmentioning
confidence: 99%
“…Uncommon secondary causes include Cushing's disease, intracranial tumour, pheochromocytoma, hyperparathyroidism and aortic coarctation. Diabetes is also a secondary cause of resistant hypertension 36,37 .…”
Section: Secondary Causesmentioning
confidence: 99%